Early Childhood Caries Among 3-5-years old Preschool at in Public and Private Kindergarten at Vientiane Municipality Lao PDR - THAMMAVONGSA, Viengsay; THAMMAVONGSA, Khambai; PHENTHAVONG, Manevone; LYVONGSA, Akhao; THAMMAVONGSA, Phouthasone; THAMMAVONGSA, Viengnakhone; THONGTURM, Vimone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objective of this study was to study the prevalence of tooth decay, the percentage of dental plaque in children's mouths, and to evaluate feeding practices, oral hygiene practices, and dental visits for children attending kindergartens in Vientiane, Lao PDR. The sample size was 345 participants and analyzed the data by using the SPSS program. The result was found that the proportion of children with dental caries was as high as 93.3%, in which 40.3% of 5-year-olds have caries, 33.6% of 4 year-olds have caries and 19.4% of 3 year-olds have caries. For the number of teeth that are carious in the upper jaw, the number 61 was 79.1% and the number 51 was 76.5%. For the lower jaw, the number of teeth that are affected more than others was tooth number 75 was 65.5% and tooth number 85 was 65.5%. Therefore, this study showed that: the teeth are most affected by caries are the front teeth of the upper jaw left and the right side, followed by the teeth on the left and right sides of the lower jaw. The lower front teeth are least affected. In addition, dental disease in children is also related to the frequency of tooth brushing that was assisted or by parental care when starting to brush teeth, feeding children with milk, especially sweet milk and candies. The study indicated that dental caries prevalence among 3-5 years old children is very high and oral hygiene very poor. Further prevention programs and more students to promote better health for young children in Lao PDR are needed.